Algae in the aerophytic habitat of Račiške ponikve cave (Slovenia) - Mulec, Janez (Natura Sloveniae, 2008)
In the cave entrance of Račiške ponikve, four selected sites with confluent algal growth and different sun irradiance levels were sampled for algological analysis. Altogether, 42 algal taxa were determined, with the highest proportion of cyanobacteria, 30 taxa (71%), followed by 8 taxa (19%) of Chlorophyta and 4 taxa (10%) of Chrysophyta. The favourable ratio of Oscillatoriales vs. Nostocales indicates that flora in Račiške ponikve cave isgenerally exposed to low photo flux. In the twilight zone of the cave, coccoid cyanobacteria prevailed. Moreover, at all sampling points algae characteristic of water and/or soil habitats were also identified besides typical aerophytic algae.
Keywords: Algae; Algae, Green; Alge; Alge zelene; Classification; Cyanobacteria; Ecosystem; Ekosistem; Fresh Water; kraške jame; List of caves in Slovenia; Rašiške Ponikve; Sladka voda